The risk of re-identification versus the need to identify individuals in rare disease research - Hansson, Mats G; Lochmüller, Hanns; Riess, Olaf; Schaefer, Franz; Orth, Michael; Rubinstein, Yaffa; Molster, Caron; Dawkins, Hugh; Taruscio, Domenica; Posada, Manuel; Woods, Simon (European journal of human genetics, 2016)
There is a growing concern in the ethics literature and among policy makers that de-identification or coding of personal data and biospecimens is not sufficient for protecting research subjects from privacy invasions and possible breaches of confidentiality due to the possibility of unauthorized re-identification. At the same time, there is a need in medical science to be able to identify individual patients. In particular for rare disease research there is a special and well-documented need for research collaboration so that data and biosamples from multiple independent studies can be shared across borders. In this article, we identify the needs and arguments related to de-identification and re-identification of patients and research subjects and suggest how the different needs may be balanced within a framework of using unique encrypted identifiers.